Psychological Health Before, During, and After an Economic Crisis : Results from Indonesia, 1993 - 2000 - Friedman, Jed; Thomas, Duncan (World Bank, Washington, DC, 2012)
The 1997 Indonesian financial crisis resulted in severe economic dislocation and political upheaval, and the detrimental consequences for economic welfare, physical health, and child education have been previously established in numerous studies. We also find the crisis adversely impacted population psychological well-being. We document substantial increases in several different dimensions of psychological distress among male and female adults across the entire age distribution over the crisis period. In addition, the imprint of the crisis can be seen in the differential impacts of the crisis on low education groups, the rural landless, and residents in those provinces that were hit hardest by the crisis. Elevated levels of psychological distress persist even after indicators of economic well-being such as household consumption had returned to pre-crisis levels suggesting long-term deleterious effects of the crisis on the psychological well-being of the Indonesian population.